المترجمات فى مصر فى الفترة من 2006 - 2014 دراسة ببلیوجرافیة ببلیومتریة - د. نهى بشیر (المجلة الدولية لعلوم المكتبات والمعلومات)
This study proposed the topic of translated books in Egypt from 2006 to2014. It was a bibliography and bolometric study that restricted, described andanalyzed the translated books in Egypt. It observed 2329 translated book. Theobjectivity trends of these translated books were studied and the linguistic trendswere studied, too. It was distributed by date of publishing and by the differentpublishers of these books to know the number of translated books at that time torecognize the periods of strength and weakness. The study followed two types ofcurricula, the historical curriculum and the bibliography or bolometric mensurationcurriculum.